Kepastian Hukum Penyelesaian Sengketa Jual Beli Di Bawah Tangan Melalui Putusan Verstek: Studi Putusan PN Cibinong Nomor 327/PDT.G/2020/PN CBI - Inah Rofikhoh; M. Sudirman (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
A private land sale and purchase agreement is an agreement made by the parties without any intervention from the Land Deed Making Officer (PPAT). Private land sale and purchase agreements often cause disputes, which in the judicial process are often decided by default. The purpose of this study is to analyze the legal certainty of disputes over private land sale and purchase agreements with default decisions in the Cibinong District Court Case Number 327/PDT.G/2020/PN CBI. The research method uses normative juridical with a case approach.